Rethinking the role of employment barriers in active labor market policy: Evidence from a fixed effects analysis - TAN, Jian Qi (Institutional Knowledge at Singapore Management University, 2022)
Using a panel dataset from a five-wave survey of participants in Singapore’s Work Support Programme (WSP) from 2010 to 2016, we quantify the cumulative negative impact of facing multiple employment barriers and demonstrate the association between the individual stressors and labor market indicators. Using a fixed effects model to reduce the confounding effects of unobservables, we find that a one standard deviation increase in the number of employment barriers brings about a 2.7 to 3.5 percentage point increase in the probability of being unemployed and a 58 SGD to 78 SGD decrease in individual earnings.